Dampak Kualitas Layanan dan Harga Jual terhadap Tingkat Kepuasan pengunjung pariwisata - Lisa Maulidia; Putri Permata Lisna (Tamasya : Jurnal Pariwisata Indonesia, 2024)
This research aims to analyze the impact of service quality and selling price on the level of satisfaction of tourism visitors. With increasing competition in the tourism industry, understanding the factors that influence customer satisfaction has become increasingly important. The method used in this research is a survey involving visitors at several tourism locations. The data collected was analyzed using statistical techniques to evaluate the relationship between service quality, selling price and visitor satisfaction. The research results show that service quality has a significant positive influence on satisfaction, while selling price also plays an important role, although the impact varies. These findings can be a reference for tourism destination managers to improve visitor experiences through improving services and adjusting prices accordingly